2019
DOI: 10.1038/s42003-019-0399-1
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA from mastics solidifies connection between material culture and genetics of mesolithic hunter–gatherers in Scandinavia

Abstract: Human demography research in grounded on the information derived from ancient DNA and archaeology. For example, the study on the early postglacial dual-route colonisation of the Scandinavian Peninsula is largely based on associating genomic data with the early dispersal of lithic technology from the East European Plain. However, a clear connection between material culture and genetics has been lacking. Here, we demonstrate that direct connection by analysing human DNA from chewed birch bark pitch mastics. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
4
33
1
2
Order By: Relevance
“…[11] For example, the derived allele of the SNP rs12785878 results in reduced expression of the DHCR7 gene causing increased concentrations of 7-dehydrocholesterol in the skin and more efficient synthesis of vitamin D 3 . [86] The SNP is and complemented with recent data, [55,56,58,[67][68][69]108] in order to create the map of migration and admixture of populations in Europe since the arrival of homo sapiens some 40 000 years ago. Phenotype information was retrieved from supplementary files of the according publications or additionally assessed following the instructions of HirisPlex-S (https:// hiris plex.erasm usmc.nl), which is a forensic DNA phenotyping tool based on an array of different marker SNPs providing additional support to the SNPs of the genes SLC24A5, SLC45A2 and OCA2.…”
Section: G Ene Ti C Variants a Sso Ciated With Vitamin D Me Tabolismentioning
confidence: 99%
“…[11] For example, the derived allele of the SNP rs12785878 results in reduced expression of the DHCR7 gene causing increased concentrations of 7-dehydrocholesterol in the skin and more efficient synthesis of vitamin D 3 . [86] The SNP is and complemented with recent data, [55,56,58,[67][68][69]108] in order to create the map of migration and admixture of populations in Europe since the arrival of homo sapiens some 40 000 years ago. Phenotype information was retrieved from supplementary files of the according publications or additionally assessed following the instructions of HirisPlex-S (https:// hiris plex.erasm usmc.nl), which is a forensic DNA phenotyping tool based on an array of different marker SNPs providing additional support to the SNPs of the genes SLC24A5, SLC45A2 and OCA2.…”
Section: G Ene Ti C Variants a Sso Ciated With Vitamin D Me Tabolismentioning
confidence: 99%
“…Most recently, re-analyses of lithic remains attributed to the oldest sequence at Huseby Klev (deep pit) revealed the presence of pressure blade technologies, which are securely dated to the hiatus and the subsequent decades (10,040-9610 cal BP). Moreover, the same study also reported on aDNA extracted from chewed birch pitch revealing that the individuals were of genetically admixed ancestry 77 . This novel lithic technology coupled with a changed bone point morphology and the pattern of radiocarbon dates from Western Sweden and Central Scandinavia 78 favours the spread of this technology through Scania and into present-day Denmark.…”
Section: Resultsmentioning
confidence: 82%
“…Ancient DNA (aDNA) has become a widely accepted source of biological data, helping to provide new perspectives for a range of fields including archaeology, cultural heritage, evolutionary biology, ecology, and palaeontology. The utilisation of short-read high-throughput sequencing has allowed the recovery of whole genomes and genome-wide data from a wide variety of sources, including (but not limited to), the skeletal remains of animals [1,2,3,4], modern and archaic humans [5,6,7,8], bacteria [9,10,11], viruses [12,13], plants [14,15], palaeofaeces [16,17], dental calculus [18,19], sediments [20,21], medical slides [22], parchment [23], and recently, ancient ‘chewing gum’ [24,25]. Improvement in laboratory protocols to increase yields of otherwise trace amounts of DNA has at the same time led to studies that can total hundreds of ancient individuals [26,27], spanning single [28] to thousands of organisms [18].…”
Section: Introductionmentioning
confidence: 99%